Catatonic Schizophrenia Associated With Cerebrospinal GAD65 Autoantibodies: Case Report and Literature Review - Hansen, Niels; Bartels, Claudia; Teegen, Bianca; Wiltfang, Jens; Malchow, Berend (Frontiers in Immunology, 2022)
Background: GAD65 autoimmunity is reported to be associated with schizophrenia and bipolar disorder. However, there has been no evidence that glutamic acid decarboxylase 65 (GAD65) autoantibodies in cerebrospinal fluid are associated with akinetic catatonia in schizophrenia patients. Methods: We report the case of a 28-year-old man who underwent diagnostics including brain magnetic resonance imaging (MRI), neuropsychological testing, and electroencephalography (EEG) as well as a tumor search via computed tomography (CT) of the abdomen and thorax, as well as coloscopy and gastroscopy. For clinical characterization, his patient files were retrospectively examined. Results: Our patient presented a catatonia that responded within hours to benzodiazepines in combination with previously taken antipsychotics such as risperidone for prediagnosed paranoid schizophrenia. Diagnostics revealed GAD65 autoantibodies in his serum and cerebrospinal fluid (CSF). MRI revealed no brain lesion, and the tumor search no malignancy. We diagnosed a catatonic schizophrenia. Furthermore, as he had not fully recovered, he was given immunotherapy entailing two cycles of intravenous immunoglobulins. Subsequent neuropsychological testing due to subjective cognitive complaints after immunotherapy revealed no objective cognitive deficits. Conclusions: We present the novel finding of an association between GAD65 autoantibodies in the serum and CSF with catatonia in a patient suffering from prediagnosed chronic schizophrenia. Due to the presence of CSF GAD65 antibodies, we suspect that his catatonia has an autoimmune origin. Immunotherapy stabilized the catatonia that had initially responded to lorazepam treatment. Further research should be done to characterize patients’ responses to immunotherapy and standard treatment in a large cohort of patients with GAD65 antibody-associated catatonia and schizophrenia.